2014
DOI: 10.1108/jea-08-2012-0100
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring vocational schools as social innovation?

Abstract: Purpose – The purpose of this paper is to conceptualize the implementation of educational reform processes by applying the concept of social innovation. The paper proposes a model of social innovation and test its applicability in the context of Estonian vocational education reform using two case studies of the school re-organization as an example. Design/methodology/approach – A case study approach has been applied in the empirical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…social innovation studies have rarely investigated how these are converted into practical transformations in the educational sector (cf. Alden-Rivers et al, 2015;Brundenius et al, 2016;Martinelli, 2013;Ümarik et al, 2014). This study therefore aims to provide further insight into the impact of contextualized and materialized norms and values in educational social innovation, using a remodeling process of preschool facilities in a Swedish municipality as an illustrating case study.…”
Section: Reconstrucción Socialmente Innovadora De Infraestructuras Preescolaresmentioning
confidence: 99%
“…social innovation studies have rarely investigated how these are converted into practical transformations in the educational sector (cf. Alden-Rivers et al, 2015;Brundenius et al, 2016;Martinelli, 2013;Ümarik et al, 2014). This study therefore aims to provide further insight into the impact of contextualized and materialized norms and values in educational social innovation, using a remodeling process of preschool facilities in a Swedish municipality as an illustrating case study.…”
Section: Reconstrucción Socialmente Innovadora De Infraestructuras Preescolaresmentioning
confidence: 99%
“…Õpetajad võivad olla muutuste suhtes skeptilised või tõrjuvad, kuna paljud haridusreformid pole lähtunud kooli ja õpetajate vajadustest (Goodson, 2010;Goodson, Moore, & Hargreaves, 2006;Müller, Norrie, Hernández, & Goodson, 2010;Rekkor et al, 2013;Vähäsantanen & Eteläpelto, 2009). Leitud on, et reformipoliitika, mis ei kaasa õpetajaid ega toeta õpetajate professionaalsust, ei ole edukas ega jätkusuutlik (Singh, 2011;Ümarik, Loogma, & Tafel-Viia, 2014).…”
Section: Kutseharidusreformiga Kaasnenud Muutuste Mõju Kutseõpetajateunclassified
“…Bonifacio, 2014);  social action (Cajaiba-Santana, 2013; Bhatt & Altinay, 2013);  social capital (Bhatt & Altinay, 2013);  social practices (Oeij et al, 2011;Cajaiba-Santana, 2013;Howaldt et.al., 2014;Klievink & Janssen, 2014);  cross-sector partnership (Le Ber & Branzei, 2010; Jiménez Escobar & Morales Gutiérrez, 2011);  relationships (OECD, 2010;Li et al, 2012;Klein et al, 2012;Nichols et al, 2013;Klievink & Janssen, 2014), etc. This literature review presents core elements and common features of social innovation (Minks, 2011;Edwards-Schachter et al, 2012;The Young Foundation, 2012;Bulut et al, 2013;Ümarik et al, 2014), typology of social innovation (Nambisan, 2009, cited in Lundstrom & Zhou, 2011; The Young Foundation, 2012; Davies, 2014) as well as fields, sectors, and levels of social innovation (The Young Foundation, 2012; Bund et al, 2013;Bonifacio, 2014). The most crucial analytical dimensions and models of social innovation which could be used in the further empirical research are determined to be:  the systemic model for social impact innovation (Ortega et al, 2014);  the conceptual model or heuristic of social innovation (McCarthy et al, 2014);  the conceptual model of the social innovation process (Cajaiba-Santana, 2013);  the relevant building blocks of innovation studies and key dimensions of social innovation (Howaldt et al, 2014);  the integrated model for measuring social innovation (Bund et al, 2013;Krlev et al, 2014);  the six stage process of social innovation (Murray et al, 2010;The Young Foundation, 2012);  the policy analytical dimensions concerning social innovation (Lundstrom & Zhou, 2011).…”
Section: State-of-the-art Review Of the Development And Research Of Smentioning
confidence: 99%
“… the citizen engagement in social innovation (Davies & Simon, 2012) including a typology for mapping citizen engagement in the social innovation process as well as functions and examples of engagement;  the structural and agency barriers to social innovation (Mendes et al, 2012). Recent studies (Pol & Ville, 2009;Edwards-Schachter et al, 2012;Cajaiba-Santana, 2013;Ümarik et al, 2014) have shown that the concept of social innovation is used in various and overlapping ways in different disciplines; the research on social innovation is highly diversified, fragmented and includes interdisciplinary approaches to social innovation from different fields such as territorial and urban development, sociology, public administration, social entrepreneurship, history, economics, social psychology, management, social movements, creativity, political science, communication technologies, environmental sciences, human services, etc.…”
Section: State-of-the-art Review Of the Development And Research Of Smentioning
confidence: 99%
See 1 more Smart Citation